1998
DOI: 10.1128/jvi.72.2.891-899.1998
|View full text |Cite
|
Sign up to set email alerts
|

Paramyxovirus RNA Synthesis and the Requirement for Hexamer Genome Length: the Rule of Six Revisited

Abstract: The template for paramyxovirus RNA synthesis is not naked RNA but the helical nucleocapsid core of the virus, in which each nucleocapsid protein (N protein) is predicted to be associated with precisely 6 nucleotides (nt) (11). Presumably as a consequence of this association, paramyxovirus genomes are replicated efficiently only when they are a multiple of 6 nt in length, and this has been dubbed the "rule of six" (4). The structure of paramyxovirus nucleocapsids is thus central to understanding how this rule m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(135 citation statements)
references
References 38 publications
3
128
0
4
Order By: Relevance
“…Nucleotide sequencing also demonstrated that a 126-nucleotide gag fragment remained after the 1.416 kb sequence was deleted, and as expected, the genome of the deletion mutant conformed to the paramyxovirus rule-of-six (Kolakofsky et al, 1998), which states that the total number of nucleotides in the genomic RNA must be a multiple of 6 to replicate efficiently. Because this truncated gag gene contained the target amplicon sequence for the gag mRNA-specific RT-qPCR assay, abundant mRNA signal was observed even as the mutant virus emerged and became a dominant species in the infected ferrets.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Nucleotide sequencing also demonstrated that a 126-nucleotide gag fragment remained after the 1.416 kb sequence was deleted, and as expected, the genome of the deletion mutant conformed to the paramyxovirus rule-of-six (Kolakofsky et al, 1998), which states that the total number of nucleotides in the genomic RNA must be a multiple of 6 to replicate efficiently. Because this truncated gag gene contained the target amplicon sequence for the gag mRNA-specific RT-qPCR assay, abundant mRNA signal was observed even as the mutant virus emerged and became a dominant species in the infected ferrets.…”
Section: Discussionsupporting
confidence: 69%
“…1A). Following gene insertion, the overall genome length followed the paramyxovirus rule-of-six (Kolakofsky et al, 1998).…”
Section: Cell Culture and Virusesmentioning
confidence: 99%
“…1A, C). Both new chimeric constructs conformed to the "rule of six" (i.e., each genome length was an even multiple of six nucleotides), and both were designed so that the hexamer spacing of transcription signals was conserved (i.e., the first and last genes, N and L, initiate at the second hexamer nucleotide while all other genes initiate at the first hexamer nucleotide) (Kolakofsky et al, 1998).…”
Section: Functional Replacement Of the Hpiv3 Hn And F Proteins By Ebomentioning
confidence: 99%
“…1. In order to maintain the genome length as a multiple of six -a requirement for efficient NDV replication [46] -additional nucleotides were introduced at the GE region. A seven-nucleotide Kozak sequence [47] for efficient translation on the upstream of ATG, two XbaI restriction enzyme sites on the upstream and downstream of gene were also introduced burgdorferi antigens.…”
Section: Generation Of Recombinant Ndvs Expressing B Burgdorferi Ospmentioning
confidence: 99%
“…Thus, the inserted gene would be expressed as a separate mRNA. Extra nucleotides were inserted at the end of the ospC or bmpA ORF transcription cassette to maintain the rule of 6 [46]. For efficient translation, a Kozak sequence [47] was also inserted before the start codon.…”
Section: Construction Of Recombinant Ndvs Expressing B Burgdorferi Amentioning
confidence: 99%